Healing Environment for Elders in the Public Health Center 54 Tadiam, Bangkok - Chatchai Yuakkhayan; Benjamas Kutintara (Asian Creative Architecture, Art and Design : ACAAD, 2025)
The Public Health Center 54 Tadiam provides primary medical and public health services in Bang Mot sub-district, Thung Khru district, Bangkok. The building has lasted for services for more than 37 years. The healing environment provided has not responded to utilization. It is not suitable for the healing. Therefore, improvement is required to facilitate the aging society. The objectives of this research were to assess the current environment and to investigate the opinions and demands of elders, elders’ relatives, and health center staff towards a physical healing environment consisting of lighting, colors, green spaces, and sound that is good for health, and air quality, and to propose a guideline for improvement. The research was conducted based on mixed methods, both qualitative and quantitative research, to assess the post-access environment and assess opinions of building users. Data were collected from a survey, observation, interview, focus group discussion, and questions. The population in the study included elders, elders’ relatives, and health center staff. There was a group of 29 key informants. The sample consisted of 93 persons, purposively selected among building users on the day the researcher collected the data. There were 5 types of research instruments, i.e. a furniture layout plan, a behavior chart, an interview form, a focus group discussion form, and a questionnaire. Qualitative data were used for content analysis. The content was grouped to make a point discovered and arrange the priority. Quantitative data were analyzed using a statistical software package. The findings from the study revealed that the existing physical healing environment that was suitable without utilization problems included outdoor green spaces and the air quality from the ventilation system. The existing physical healing environment that was not suitable for functional problems included lighting, colors, and indoor noise. The healing environment that was not available included indoor green spaces, sound that is good for health, and air quality filling (aromatherapy). Found issues included inadequate natural light and light bulbs, which did not meet the standards. The color tone used inside the building was not suitable. There was no green space inside the building, only outdoors. Queue calling was disturbed by noises from talking in the building. Good sounds for health were not available. There was no unpleasant smell in the air, but aromatherapy was not available. Regarding opinions and demands, the current lighting is moderately sufficient for utilization. The suitable color tone is green. Green spaces are preferred. More than half of the participants required sounds that are good for health and aromatherapy from herbal essential oils that have healing properties. They expressed moderate satisfaction with the current air quality and healing environment. The Public Health Center 54 Tadiam should improve the physical healing environment as follows: signs asking for cooperation in not making a loud noise should be attached, the air quality should be increased by providing aromatherapy from herbal essential oils, indoor green spaces should be available, indoor lighting should be increased for sufficient utilization, the wall color should be changed from brown to a lighter tone.
Keywords: Urban Green Space and Health; Architecture and Cultural Influences; Architectural and Urban Studies